Akhlaq Education Values in Islamic Perspective: An Examination from the Ulama’s Books - Yatim, Mansur; Syafe'i, Imam; Amiruddin, Amiruddin (Journal of Advanced Islamic Educational Management, 2023)
This study aims to explore and analyze the values of akhlaq education from an Islamic perspective, especially those found in two important works, namely Kitab Sullam Taufiq by Shaykh Abdullah bin Husain Ba'alawi and Kitab Nasoikhul 'Ibad. Through a literature review approach, this research explores various concepts of akhlaq, character development, and ethical values found in the two books. This research methodology uses text and content analysis approaches to evaluate the teaching of akhlaq in these works. The search results present a series of values essential in shaping human character per Islamic teachings, such as patience, honesty, generosity, and self-control. The research also discusses the practical implementation of these values in the context of modern education, highlighting their relevance in shaping a noble and responsible generation. The implications of this understanding are integrated into the current educational context, offering an in-depth perspective on how Islamic akhlaq values can be applied in formal and informal education. This research contributes to broadening the understanding of the values of akhlaq education in Islam as well as providing a foundation for the development of educational strategies that focus on character-building rooted in Islamic teachings